Global change and local places : estimating, understanding, and reducing greenhouse gases (Cambridge University Press, 2003)
How do our everyday lives affect climate change? This book compares four different sites in the United States, and looks at the human factors affecting climate change (such as greenhouse gas emissions), how these factors are changing, and what can be done to mitigate the effects at a local level.